The variability of common reed Phragmites australis (Cav.) Trin. ex Steudel populations growing in urban conditions - Krzakowa, Maria; Jakubiak, Hanna; Kołodziejczak, Mirosława (Ecological Questions, 2008)
Differences between 13 common reed (Phragmites australis) populations, growing in urban conditions within the town of Poznań (western Poland), are described by 8 morphological traits of panicles’ variability and the frequency of peroxidase (dimeric and monomeric) allozymes. Values of morphological characters were processed statistically using agglomerative clustering by the closest neighbours (UPGMA) method based on Euclidean distances. Proteins were separated in the starch gel electrophoretic procedure, showing cathodic migration. Populations are polymorphic and have a certain level of heterozygosity. The level of populations’ diversity (DST = 0.097) is lower than the intra-population variability (GST = 0.187). The gene flow between populations is rather low (Nm = 1.090).